(untitled) (Research, Society and Development, 2020)
This study sought to identify in the literature the scientific evidence on the use of information and communication technologies in the teaching of undergraduate nursing. An integrative literature review was carried out between 2014 and 2018, on the basis of Latin American and Caribbean Literature in Health Sciences; International Health Sciences Literature; US Nursing Database and National Library of Medicine National Institutes of Health. Descriptors used: nursing, educational technology, information technology. As results, 1001 studies were found, of which 18 met the inclusion criteria, from which 3 analytical categories emerged, namely: the use of simulation in the practice of nursing education; case-based learning and technological support; and active methodologies. It was concluded that the teaching characteristics are focused on the use of technologies, which includes the student in the protagonism of his learning, so that he can make the best decisions in nursing care. The study aims to contribute to the field of nursing, with regard to the valuation of teaching in times where critical thinking includes the ability to reason and think logically, analyze, judge situations appropriately and act on a reasoned basis.